PEMAKAIAN PRODUK FEMININE DAILY CARE PADA REMAJA WANITA DI DUSUN SONGSONG DESA ARDIMULYO KECAMATAN SINGOSARI KABUPATEN MALANG - Meilinda Dwi Trisutanti (Jurnal Kesehatan Hesti Wira Sakti, 2020)
Feminine Daily Care is a hygiene product for female genital area which used by women to clean their genital area when they face several conditions such as secrete mucus or when their genitals smells bad. Feminine daily care that commonly used among teenagers are panty liners, herbal sanitary pads, betel leaf, and feminine soap. The use of feminine daily care product is not recommended to be used every day because there is the normal flora inside female genital area (Ryani, 2018). The effect that may occur due to the overuse of feminine daily care product are infection and dangerous for genital area. The purpose of this research is to find out the attitude of teenagers at Dusun Songsong Desa Ardimulyo about the use of feminine daily care product. The research conducted using descriptive study. The population of the study was 270 teenagers at Dusun Songsong Desa Ardimulyo. The sampling method used in this research was purposive sampling, and the sample of the study was 65 girl teenagers from Dusun Songsong Desa Ardimulyo on January 2021. The variable measured in this research was the attitude of teenagers in using feminine daily care. The data collected by using questionnaire through Google Form. Univariat analysis was used in this research. The data from the research described the attitude of teenagers at Dusun Songsong Desa Ardimulyo towards the use of feminine daily care product as follows: 9 teenagers (14%) showed good attitude towards the use of feminine daily care product, half of the teenagers, 23 teenagers (35%) showed fair attitude and most of the teenagers, 33 person (51%) showed low attitude towards the use of feminine daily care product. The factors that probably affected the result of the data are: age, menarche age, education level, and their understanding about the information about the product. Based on the result of the research, the researcher hoped that teenagers could gain better understanding about the use of feminine daily care product and establish good behavior. Keywords: attitude, teenagers, the use of feminine daily care.